Acute Idiopathic Scrotal Edema: Systematic Literature Review - Santi, Maristella; Lava, Sebastiano A. G.; Simonetti, Giacomo D.; Bianchetti, Mario G.; Milani, Gregorio P. (European Journal of Pediatric Surgery, 2018)
Introduction Existing information on acute idiopathic scrotal edema relies on small case series and textbooks.Methods We searched reports with no date limits on acute idiopathic scrotal edema.Results Thirty-seven studies were included. Sixteen case series addressed the prevalence of acute idiopathic scrotal edema among males with acute scrotum: among 3,403 cases, the diagnosis of acute idiopathic scrotal edema was made in 413 cases (12%). Twenty-four reports addressed history, findings, management, and course of acute idiopathic scrotal edema in 311 patients. The patients mostly ranged in age from 5 to 8 years, presented with acute scrotal redness and swelling, associated or not with mild pain. Ninety percent or more of the cases developed in patients without atopic diathesis and were not preceded by inguinoscrotal surgery, acute febrile illnesses, or trauma. They were afebrile; in good general condition; and presented without pruritus, nausea or vomiting, or abdominal pain. The lesions were bilateral in two-thirds and unilateral in one-third of the cases. The condition resolved spontaneously within 2 to 3 days without sequelae. Approximately 10% of the cases experienced a recurrence.Conclusion Acute idiopathic scrotal edema is a self-limiting condition that accounts for ≥ 10% of cases of acute scrotum in children and adolescents.
Keywords: acute scrotum; acute idiopathic scrotal edema; scrotal redness and swelling; imaging studies